HUBUNGAN MASSA BEBAS LEMAK DAN LAJU METABOLIK BASAL DENGAN HANDGRIP STRENGTH MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA TAHUN 2023 - Noor Az Zhahra, (2024)
Hand grip strength is an indicator that tests muscle strength and is considered a predictor of sarcopenia or loss of muscle mass. Muscle mass is a constituent of fat-free mass (FFM) and FFM is the main determinant of basal metabolic rate (BMR). Medical students tend to have a lifestyle that causes a decrease in muscle strength, which can increase risk factors for cardiovascular disease, metabolic syndrome, type 2 diabetes mellitus, and sarcopenia. This study aims to determine the relationship between fat-free mass and basal metabolic rate with grip strength of students at the Faculty of Medicine, University of Pembangunan Nasional "Veteran" Jakarta in 2023. The research used a cross-sectional design, sample size was 54 students according to the research criteria, and purposive sampling technique. Handgrip strength was measured using a handgrip dynamometer. Fat free mass and basal metabolic rate were measured using Bioelectrical Impendance Analysis (BIA). The results of the Independent sample t-test showed that there was no significant difference based on fat-free mass between respondents with low hand grip strength and low hand grip strength (p = 0.662). The results of the Chi-square test showed that there was a significant relationship between basal metabolic rate and hand grip strength (p = 0.001; OR = 16.875). Medical faculty students need to maintain activity performance, train muscle strength, and adopt a healthy lifestyle so that handgrip strength, fat-free mass, and basal metabolic rate are maintained.